2012
DOI: 10.1029/2012gl052103
|View full text |Cite
|
Sign up to set email alerts
|

The structure of Fe‐Ni alloy in Earth's inner core

Abstract: The crystal structure of Fe‐10%Ni was investigated up to 340 GPa and 4700 K, corresponding to the Earth's inner core conditions by synchrotron X‐ray diffraction measurementsin‐situat ultrahigh pressure and temperature in a laser‐heated diamond‐anvil cell. The results show that hexagonal closed‐packed (hcp) structure is stable throughout the experimental conditions investigated with no evidence for a phase transition to body‐centered cubic (bcc) or face‐centered cubic (fcc) phases. The axialc/a ratio of the hcp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 33 publications
5
48
1
3
Order By: Relevance
“…axial ratio increased with increasing temperature, but the temperature effect was small. Compared with the previous data on pure Fe and Fe-10 wt.% Ni alloy obtained at ∼330 GPa (Tateno et al, 2010(Tateno et al, , 2012, Fe-9 wt.% Si alloy exhibited relatively high c/a ratio. The earlier data obtained at 80 GPa (Lin et al, 2002) show markedly higher values, but such difference can be explained by a pressure effect (Tateno et al, 2010).…”
Section: Axial Ratio Of Hcp Fe-si Alloycontrasting
confidence: 38%
See 2 more Smart Citations
“…axial ratio increased with increasing temperature, but the temperature effect was small. Compared with the previous data on pure Fe and Fe-10 wt.% Ni alloy obtained at ∼330 GPa (Tateno et al, 2010(Tateno et al, , 2012, Fe-9 wt.% Si alloy exhibited relatively high c/a ratio. The earlier data obtained at 80 GPa (Lin et al, 2002) show markedly higher values, but such difference can be explained by a pressure effect (Tateno et al, 2010).…”
Section: Axial Ratio Of Hcp Fe-si Alloycontrasting
confidence: 38%
“…Temperature variations within such 6 μm spot were less than ±10% below 5000 K and ±15% at higher temperatures as shown in supplementary Fig. S2 ( Tateno et al, 2010Tateno et al, , 2012. It is noted that the peak temperature rather than the average temperature might be important for the appearance of the B2 phase.…”
Section: High P-t Experiments For Fe-9 Wt% Simentioning
confidence: 84%
See 1 more Smart Citation
“…After composition we discuss thermal properties, followed by transport properties, which must be calculated for specific (P, c, T ) conditions. however, recent experiments found that adding up to 10% of Ni does not change the hexagonal close-packed crystal structure of the solid 42 , while ab initio calculations suggest that at high T the seismic properties of Fe-Ni alloys are almost indistinguishable from those of pure iron 43 . Recent studies of core composition [44][45][46] given in section 1 of Table 1; each model is named after the corresponding molar concentration.…”
Section: Materials Properties For Earth's Corementioning
confidence: 92%
“…The preferred crystallographic orientation in all cases is thought to permit more efficient removal of solute from the boundary. Iron alloys in the inner core appear to have an hcp structure (Tateno et al, 2012), so similar processes should align the c-axes in horizontal planes. The strongest component of flow above the inner core is east-west, but there would also be a smaller poleward component in the northern and southern hemispheres.…”
Section: Implications For Inner-core Anisotropymentioning
confidence: 99%